2023
DOI: 10.1002/chem.202300080
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Product Inhibition in DNA Self‐Replication: Insights for Prebiotic Replication from the Role of the Enzyme in Lesion‐Induced DNA Amplification**

Abstract: Self‐replication of nucleic acids in the absence of enzymes represents an important and poorly understood step in the origin of life as such reported systems are strongly hindered by product inhibition. Studying one of the few successful examples of enzymatic DNA self‐replication based on a simple ligation chain reaction, lesion‐induced DNA amplification (LIDA), can shed light on how this fundamental process may have originally evolved. To identify the unknown factors that lead LIDA to overcome product inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Moreover, the self-replication of Triangle 72 was faster than for the analogous 18mer DNA duplex by LIDA (Figure S3), which could be attributed to a higher effective concentration from intramolecular cyclization. Consistent with our work on DNA duplex self-replication, ,, we found that the rate of self-replication of these nanoassemblies by LIDA was highly temperature dependent (Figure S4). At 22 °C, the kinetics of the reaction was very slow yielding ∼40% conversion of Linear 72 to Triangle 72 after 240 min.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Moreover, the self-replication of Triangle 72 was faster than for the analogous 18mer DNA duplex by LIDA (Figure S3), which could be attributed to a higher effective concentration from intramolecular cyclization. Consistent with our work on DNA duplex self-replication, ,, we found that the rate of self-replication of these nanoassemblies by LIDA was highly temperature dependent (Figure S4). At 22 °C, the kinetics of the reaction was very slow yielding ∼40% conversion of Linear 72 to Triangle 72 after 240 min.…”
mentioning
confidence: 91%
“…Previous work indicated cyclization over polymerization was observed at ≤5 μM concentration, consistent with our results performed at 1.4 μM DNA. 24 Significantly this concentration has been shown in LIDA to lead to rapid self-replication 20,25,26 suggesting that this concentration should facilitate the selfreplication of nanoassemblies (Scheme 1).…”
mentioning
confidence: 97%
See 1 more Smart Citation